Fluorescence In Situ Hybridization for Glycine max Metaphase Chromosomes. Issue 1 (3rd March 2017) - Findley, Seth D.; Birchler, James A.; Stacey, Gary
Abstract: This article presents protocols for fluorescence in situ hybridization (FISH) in the cultivated soybean, Glycine max . The protocols represent soybean‐optimized versions developed for maize. We describe the use of two different probes types: genomic‐repeat‐based fluorescently‐tagged oligonucleotides and bacterial artificial chromosomes (BACs). The two probe types can be used either individually or together, depending on the experimental questions. The article also includes starting points for executing FISH in additional legume species. © 2017 by John Wiley & Sons, Inc.